Productivity Study of the Scaffolding Operations in Liquefied Natural Gas Plant Construction: Ichthys Project in Darwin, Northern Territory, Australia - Moon, S.; Forlani, J.; Wang, Xiangyu; Tam, V. (American Society of Civil Engineers, 2016)
Natural gas usage has increased steadily over the past decades, in line with society's demands for this resource. In turn, allied industries face the challenge of meeting construction needs for required structures, including product facilities, pipe lines, on/offshore platforms, and marine jetties. Subsequently, these structures require huge amounts of scaffolding to facilitate their construction and maintenance. As such, this research project focused on the opportunity for the civil/construction discipline to cooperate with natural gas facility construction, more specifically productivity studies on their scaffolding operations. The productivity study in this paper presents an investigation of the effect of resource configurations on on-site measures during a scaffolding operation on an actual liquefied natural gas (LNG) plant construction, which, in turn, aims for the continuous improvement of relevant worker performance. The discussion details the quantified effect of different scaffold logistics: (1) scaffolding types, (2) scaffolding dimensions, and (3) material resource types. For instance, the system scaffolding as one of the material resource types shows less time spent than the conventional scaffolding's performance (95.1-85.2=9.9 min/m2) during the erection phase. Finally, the research findings highlight the civil/construction engineers' obligations in LNG plant projects with an emphasis on its scaffolding needs.